Umbilical artery pulsatility index reference chart selection - Diez Chang, Guillermo (2021)
Umbilical arteries (UA) resistance is assessed to detect growth restriction due to an inadequate placentation in small infants at risk of perinatal death and longterm incapacity. The umbilical artery pulsatility index (UA PI) must be compared with a statistically selected reference chart. Objective: To identify the pulsatility index (PI) reference curve whose critical value best matches our population data. Methods: The cohort was described in a previous study of 1 753 fetuses with 2 031 measurements of the PI of the uterine arteries and umbilical arteries with normal maternal-perinatal outcome. Results: PI UA had a significant negative correlation (r= -0.42) with gestational age (GA). The 95th percentile of our patients was significantly different from those published by Arduini, Acharya, Ciobanu, Baschat and Limay. Conclusion: The umbilical artery pulsatility index figures obtained conform better to Parra’s reference curves.